Development of Worksheet Based on Problem Based Learning (PBL) to Improve Critical Thinking Skills - Handayani, Ruri; Lestari, Fitria; Marian, Fungky (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study develops a Problem-Based Learning (PBL)-based Student Activity Sheet (Worksheet) to enhance students' critical thinking skills. Using the Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), the research involved Grade VII students at Nurul Iman Integrated Islamic Middle School. Data collection employed validation sheets, student response questionnaires, critical thinking tests, and observation and interview guidelines, analyzed through Miles & Huberman’s framework. Results indicate that the developed PBL-based Worksheet is of high quality, validated by material experts (average score: 137.5) and media experts (100.5). Student responses rated its practicality as good (score: 80). A Paired Sample T-Test showed a significant improvement in students’ critical thinking skills, with a 41% increase (moderate category). Comparisons with previous studies highlight the Worksheet’s novelty, while addressing limitations—such as sample size, intervention duration, and generalizability—would enhance its academic rigor. The findings suggest that integrating PBL-based Worksheets into instruction effectively supports critical thinking development. Further research should explore its applicability across different educational levels and examine the potential integration of technology.